Immune-modulating properties of ionizing radiation: rationale for the treatment of cancer by combination radiotherapy and immune checkpoint inhibitors - Derer, Anja; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (Cancer Immunology Immunotherapy, 2016)
Radiotherapy (RT) utilizes the DNA-damaging properties of ionizing radiation to control tumor growth and ultimately kill tumor cells. By modifying the tumor cell phenotype and the tumor microenvironment, it may also modulate the immune system. However, out-of-field reactions of RT mostly assume further immune activation. Here, the sequence of the applications of RT and immunotherapy is crucial, just as the dose and fractionation may be. Lower single doses may impact on tumor vascularization and immune cell infiltration in particular, while higher doses may impact on intratumoral induction and production of type I interferons. The induction of immunogenic cancer cell death seems in turn to be a common mechanism for most RT schemes. Dendritic cells (DCs) are activated by the released danger signals and by taking up tumor peptides derived from irradiated cells. DCs subsequently activate T cells, a process that has to be tightly controlled to ensure tolerance. Inhibitory pathways known as immune checkpoints exist for this purpose and are exploited by tumors to inhibit immune responses. Cytotoxic T lymphocyte antigen 4 (CTLA-4) and programmed cell death protein 1 (PD-1) on T cells are two major checkpoints. The biological concepts behind the findings that RT in combination with anti-CTLA-4 and/or anti-PD-L1 blockade stimulates CD8+ T cell-mediated anti-tumor immunity are reviewed in detail. On this basis, we suggest clinically significant combinations and sequences of RT and immune checkpoint inhibition. We conclude that RT and immune therapies complement one another.
EVALuna2:18336